Saving and Investment in Euroland, the EU and the enlarged EU - Gianpaolo Rossini; Paolo Zanghieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
The Feldstein-Horioka puzzle has been recently included among the six major puzzles of international economics. It is a paradox that belongs to the large group of home biases that have become stylized facts. We investigate the F-H puzzle according to dierent definitions of Europe and by introducing a more suitable investment variable that results after netting out FDI. We find that the F-H coeficient decreases in all cases in whcih we adopt the correct investment definition. Over time we see a decrease of the F-H coeficient during the 1980's and an increase over the 1990's as a proof that the Maastricht Treaty discipline has made current account targeting biting. This does not happen for opting out and Eastern Europe countries.
Keywords: 330